Dampak pengangguran terhadap tingkat kemiskinan di indonesia - Aditya, Rengga (Maliki Interdisciplinary Journal, 2025)
This study discusses the impact of unemployment on poverty levels in Indonesia. Unemployment is a significant economic issue that contributes to widespread poverty. In this research, we explore the relationship between unemployment and poverty, as well as the factors influencing both. Data shows that high unemployment rates negatively affect family income, hindering their ability to meet basic needs. Furthermore, the analysis indicates the need for reforms in the education system and labor policies to create quality jobs. This research aims to provide effective policy recommendations to reduce unemployment and enhance community welfare. High unemployment rates not only reduce individual income but also impact the well-being of families as a whole. Families with unemployed members tend to struggle to meet basic needs, contributing to an increase in the number of individuals living below the poverty line.